5x-3(2x+7)=2x+9
This is the equation and Raul had to solve it for x
So he started with simplifying the parenthesis first
To simplify the parenthesis -3 gets multiplied with 2x and 7 , to get rid of parenthesis
So it came out to be
5x-3(2x+7)=2x+9
STEP-1
5x-6x -21 = 2x+9 , So the STEP-1 is correct,
After this in Step -2 , he has combined the like terms on left side, the like terms are 5x and -6x , 5x-6x should combine to -x , because 5-6 = -1
So
STEP-2
-x -21 = 2x+9 , So STEP -2 is INCORRECT
So he made a mistake in STEP-2
After that subtract 2x from both sides
-3x -21 = 9
add 21 to both sides
-3x = 30
divide both sides by -3
x=-10
Hence Option B is correct , he made a mistake in STEP -2